Employers' Perception Of Competences Acquired Through Academic Marketing Training In Knowledge Based Economy - Ioan Plăiaş; Ciprian-Marcel Pop; Raluca Băbuţ; Dan Cristian Dabija (Amfiteatru Economic Journal, 2011)
One of the current concerns of the academic environment in economics is highlighting the importance of competences that higher education graduates should display when they step across the threshold of the real economy. To this effect, the identification of those competences which are compatible with the needs of the real economy may serve as a solid basis for developing adequate curricula and obtaining remarkable educational outcomes reflected in the graduates' performance as entry level employees. It is undeniably true that the said competences must meet the standards set by the real economy or by the regulations of accreditation bodies. The process by which these standards are defined or identified requires a strong sense of coherence between the academic curriculum and the needs of employers, as basis for the graduates' comprehensive training in knowledge based economy. In this context, we set to conduct an exploratory research by means of which we may emphasize how the corporate world perceive the marketing training received by the entry-level employees as graduates of professional higher education institutions, and how to adjust the curriculum to improve graduates employability. The survey was conducted by using the face-to-face questionnaire administration. Data were collected in the Transylvania counties during October 2010, as part of a field survey. The employer's perception, as highlighted by the answers received from the surveyed corporate entities, gives us reasons to state that practical experience cannot be substituted for the academic training in knowledge based economy; it can, however, strengthen its fundamental role in establishing the guidelines of moral and professional conduct such as learning and the theoretical approach to some practical situations of the real economy. Moreover, we appreciate that a continuous correlation between the practical needs and the academic training is imperative.
Keywords: M1; M3; M31; 330; competences; academic curricula; marketing training; perception; graduates